Corporate Liability for Foreign Corrupt Practices under Canadian Law - Blyschak, Paul (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2014)
Compliance with, and risk management in respect of, foreign anti-corruption law has quickly become a priority for Canadian corporations with international operations or assets. This article tracks this rapid evolution in Canadian corporate culture and compliance through a broad examination of corporate liability for foreign corrupt practices under Canadian law. Rather than merely conduct a review of the law governing corporate liability for foreign corrupt practices under Canadian law, however, this article also highlights a number of unresolved, problematic, or more complex areas of such law. This review does not purport to the exhaustive; nor does it presume offer definitive answers to the numerous questions posed. Rather, given the recent acceleration of the enforcement of the CFPOA by Canadian authorities, the aim of this article is to contribute novel legal analysis to an increasingly important area of corporate law and practice.